The Theological Methodology of John Oman and H. H. Farmer - Langford, Thomas A. (Religious studies, 1966)
Two successive theologians at Westminster College, Cambridge, John Oman and Herbert H. Farmer, represented a distinctive theological development which extended over fifty years of the present century. Oman with his original mind was the inaugurator; Farmer was the disciple who followed with great devotion, but who also exhibited independence and attempted to bring his teacher's insight into creative relation with later theological emphases, especially with the renewed interest in Christology.